Establishing a Paradigm: A Systematic Analysis of Interactive Advertising Research. Issue 1 (2nd January 2017) - Daugherty, Terry; Djuric, Vanja; Li, Hairong; Leckenby, John
ABSTRACT: This study presents a review of the advertising literature published in the Journal of Interactive Advertising ( JIAD ) through the application of a paradigm funnel. The technique is designed to systematically explore, classify, and analyze a body of work to gain insight into the current status of a research paradigm. Subsequently, interactive advertising is defined within a scholarly framework and more than 186 research articles are evaluated. The results provide a foundation for helping advertising scholars identify patterns, existing gaps in the literature, and research opportunities for the future that will expand our understanding of interactive advertising.